2009
DOI: 10.1128/jvi.00296-09
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexual Transmission of Human Immunodeficiency Virus Type 1 Subtype C: Macrophage Tropism, Alternative Coreceptor Use, and the Molecular Anatomy of CCR5 Utilization

Abstract: Human immunodeficiency virus type 1 transmission selects for virus variants with genetic characteristics distinct from those of donor quasispecies, but the biological factors favoring their transmission or establishment in new hosts are poorly understood. We compared primary target cell tropisms and entry coreceptor utilizations of donor and recipient subtype C Envs obtained near the time of acute infection from Zambian heterosexual transmission pairs. Both donor and recipient Envs demonstrated only modest mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
84
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 58 publications
12
84
2
Order By: Relevance
“…This was in sharp contrast to the two macrophage-tropic strains, HIV-1 BaL and HIV-1 NL4-3.YU2 that showed equal infectivity in both cell types. These data confirm previous studies using both MDM and CD4 ϩ T cells (11,18,20,21).…”
Section: Resultssupporting
confidence: 82%
“…This was in sharp contrast to the two macrophage-tropic strains, HIV-1 BaL and HIV-1 NL4-3.YU2 that showed equal infectivity in both cell types. These data confirm previous studies using both MDM and CD4 ϩ T cells (11,18,20,21).…”
Section: Resultssupporting
confidence: 82%
“…The CCR5-tropism of the viruses reported here matched the V3-loop based algorithm, which stipulates that a high-positive charge of V3 and basic residues at positions 306, 321 and/or 322 is required for CXCR4 tropism (Cardozo et al, 2007;Xiao et al, 1998). Alternative coreceptors (CCR1, CCR2b, CCR3, CCR8 and APJ) were tested but efficient cellular entry was rare, in agreement with other recently published studies on coreceptor usage by subtype C Envs except that we recorded lower use of APJ (Isaacman-Beck et al, 2009; Nedellec et al, 2009). Only 1/18 Envs yielded a notable level of infection on CCR1-, 2/18 on CCR8-and 4/18 on CCR3-expressing cells (Table 1; the cut off for significant infection was set to ¢10 % of the level on CCR5-expressing indicator cells).…”
supporting
confidence: 78%
“…In this context, it is critical to know whether transmitted viruses possess unique biological properties that predispose them to establish new infections more efficiently. This is a controversial topic, because some studies have reported TF-specific traits (22,24,26,52,(55)(56)(57), whereas others have failed to confirm these results (27,28,53,58,59). Some of these discrepancies are likely due to the fact that most previous analyses did not compare HIV-1 strains from transmission pairs.…”
Section: Discussionmentioning
confidence: 52%